Vascular smooth muscle cells exhibit elevated hypoxia-inducible Factor-1α expression in human blood vessel organoids, influencing osteogenic performance - da Silva Feltran, Geórgia [UNESP] (2024)
Considering the importance of alternative methodologies to animal experimentation, we propose an organoid-based biological model for in vitro blood vessel generation, achieved through co-culturing endothelial and vascular smooth muscle cells (VSMCs). Initially, the organoids underwent comprehensive characterization, revealing VSMCs (α-SMA + cells) at the periphery and endothelial cells (CD31+ cells) at the core. Additionally, ephrin B2 and ephrin B4, genes implicated in arterial and venous formation respectively, were used to validate the obtained organoid. Moreover, the data indicates exclusive HIF-1α expression in VSMCs, identified through various methodologies. Subsequently, we tested the hypothesis that the generated blood vessels have the capacity to modulate the osteogenic phenotype, demonstrating the ability of HIF-1α to promote osteogenic signals, primarily by influencing Runx2 expression. Overall, this study underscores that the methodology employed to create blood vessel organoids establishes an experimental framework capable of producing a 3D culture model of both venous and arterial endothelial tissues. This model effectively guides morphogenesis from mesenchymal stem cells through paracrine signaling, ultimately leading to an osteogenic acquisition phenotype, with the dynamic involvement of HIF-1α.